(untitled) (Eurasian Research Bulletin, 2023)
This paper makes analyses of the arterial hypertension as a sign of disorder of the cardiovascular system in children and adolescents with overweight and obesity. On this case, research has pinpointed on the various features of the research from both theoretical and methodological points. In conclusion, research has declared outcomes and shortcomings over the obesity topic.